2017
DOI: 10.1021/acs.biomac.7b01311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Functional Groups on the Oxidation State and Interfacial Binding Property of Catechol-Based Adhesive

Abstract: Adhesive hydrogels were prepared by copolymerizing dopamine methacrylamide with either acrylic acid (AAc) or N-(3-aminopropyl)methacrylamide hydrochloride (APMH). The effect of incorporating the anionic and cationic side chains on the oxidation state of catechol was characterized using the FOX assay to track the production of hydrogen peroxide byproduct generated during the autoxidation of catechol, and the interfacial binding property of the adhesive was determined by performing Johnson-Kendall-Roberts contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 62 publications
0
59
0
Order By: Relevance
“…With the sequence-controlled oligomers we could additionally show the effect of catechol/amine spacing. In case where the catechol and amine residues are in close vicinity (11), the adhesion energy is drastically amplied compared to the oligomers with an additional EDS spacer between catechol and amine (6 and 9). In addition, the adhesion was affected by changing the position of the catechol and amine residues (6 and 9).…”
Section: Scp Preparation and Adhesion Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the sequence-controlled oligomers we could additionally show the effect of catechol/amine spacing. In case where the catechol and amine residues are in close vicinity (11), the adhesion energy is drastically amplied compared to the oligomers with an additional EDS spacer between catechol and amine (6 and 9). In addition, the adhesion was affected by changing the position of the catechol and amine residues (6 and 9).…”
Section: Scp Preparation and Adhesion Measurementsmentioning
confidence: 99%
“…Such synergy between catechol (DOPA) and charged groups could be conrmed using synthetic polymers combining anionic and cationic residues. [11][12][13] Inspired by the adhesive properties of the Mfps, a wide range of polymers with high DOPA content were synthesized toward advanced adhesives and surface coatings. 1,6,[14][15][16][17][18][19][20][21][22][23] However, sequence effects like the spacing of the charged groups and catechol residues were given little attention for the design of such mussel-inspired synthetic adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of cationic functional group to catechol groups containing adhesion elevate the interfacial binding to various inorganic substrate [101,102,103]. Narkar et al [104] have made a systematic study about the effect of ionic side chain on oxidation state and interfacial binding property of catechol-functionalized hydrogel. They prepared adhesive hydrogels by copolymerizing dopamine methacrylamide (DMA) with either acrylic acid (AAc) or N -(3-aminopropyl)methacrylamide hydrochloride (APMH).…”
Section: Interactions Of Catechol-functionalized Hydrogels On Thementioning
confidence: 99%
“…Dopamine has strong adhesive abilities because of its catechol functional group and the terminal amino functional group of lysine. 47 Dopamine is capable of self-polymerization in an alkaline solution, forming a highly viscous PDA layer on the surface of the material. 48 Many studies have shown that PDA coating can greatly improve the hydrophilicity and biocompatibility of biomaterials.…”
Section: Histological Analysis Of Skin Repairmentioning
confidence: 99%